2019
DOI: 10.1177/0890334419875944
|View full text |Cite
|
Sign up to set email alerts
|

Do Expectant Mothers’ Breastfeeding Plans Influence Provider Prenatal Contraceptive Counseling?

Abstract: Background: Breastfeeding and optimal birth spacing are associated with improved maternal and infant health outcomes worldwide. Provision of contraceptive advice that is aligned with recommendations for breastfeeding has potential to maximize maternal and infant health. Although there is broad agreement regarding the breastfeeding compatibility of specific postpartum contraceptive methods, it is not known whether maternal breastfeeding intention influences prenatal provider contraceptive counseling. Research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although several studies have shown that contraception affects breastfeeding, few have addressed the effect of intention to breastfeed on contraception [ 24 , 25 ]. We found that intention to breastfeed increased the odds of highly effective contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown that contraception affects breastfeeding, few have addressed the effect of intention to breastfeed on contraception [ 24 , 25 ]. We found that intention to breastfeed increased the odds of highly effective contraceptive use.…”
Section: Discussionmentioning
confidence: 99%